Early disruption of photoreceptor cell architecture and loss of vision in a humanized pig model of usher syndromes. Issue 4 (7th March 2022) - Grotz, Sophia; Schäfer, Jessica; Wunderlich, Kirsten A; Ellederova, Zdenka; Auch, Hannah; Bähr, Andrea; Runa‐Vochozkova, Petra; Fadl, Janet; Arnold, Vanessa; Ardan, Taras; Veith, Miroslav; Santamaria, Gianluca; et al.
Abstract: Usher syndrome (USH) is the most common form of monogenic deaf‐blindness. Loss of vision is untreatable and there are no suitable animal models for testing therapeutic strategies of the ocular constituent of USH, so far. By introducing a human mutation into the harmonin‐encoding USH1C gene in pigs, we generated the first translational animal model for USH type 1 with characteristic hearing defect, vestibular dysfunction, and visual impairment. Changes in photoreceptor architecture, quantitative motion analysis, and electroretinography were characteristics of the reduced retinal virtue in USH1C pigs. Fibroblasts from USH1C pigs or USH1C patients showed significantly elongated primary cilia, confirming USH as a true and general ciliopathy. Primary cells also proved their capacity for assessing the therapeutic potential of CRISPR/Cas‐mediated gene repair or gene therapy in vitro . AAV‐based delivery of harmonin into the eye of USH1C pigs indicated therapeutic efficacy in vivo . Synopsis: The full phenotypic spectrum of Usher Syndrome is reflected in a pig model carrying a patient‐specific mutation after partial humanization of the porcine USH1C gene. Retinal function in USH1C pigs was improved when harmonin expression was reconstituted by AAV‐mediated gene therapy. Partial humanization of the porcine USH1C gene was facilitated by the high degree of sequence conservation in the N‐terminal region of harmonin. Vision loss within the first year of life in USH1C pigs was consistently indicated by behavior tests, clinical examination and morphological analysis. Early onset of vision loss was correlated to disrupted photoreceptor cell architecture. Ciliopathy mechanisms and their therapeutic correction were investigated in primary cells of USH1C individuals. Local application and therapeutic efficacy of AAV‐mediated treatments was examined in USH1C pigs in vivo . Abstract : The full phenotypic spectrum of Usher Syndrome is reflected in a pig model carrying a patient‐specific mutation after partial humanization of the porcine USH1C gene. Retinal function in USH1C pigs was improved when harmonin expression was reconstituted by AAV‐mediated gene therapy.